Pengembangan Program Pembelajaran Madrasah Diniyah Selasa Bersholawat Guna Memotivasi Peserta Didik di Desa Tegalrejo - Dwi Putri Yunitasanti; Mariana Mariana (Social Science Academic, 2023)
This service aims to explore and analyze student motivation while participating in learning at madrasah diniyah. The results of the research can be summarized as follows: Learning at madrasah diniyah uses the ummi method, sorogan method, rote method, demonstration method/practice of worship while the motivating factors for students to take lessons at madrasah diniyah in Tegalrejo Hamlet are intrinsic factors which consist of interest, and self-strength then extrinsic factors consisting of parents, society, and learning environment. Motivation is a form of encouragement so that students are more enthusiastic in participating in learning activities. One form of the program is Tuesday Bersholawat which is held every Tuesday. This program is aimed at students at Madrasah Diniyah Nurul Mutaqin. The method used in this service is a qualitative method. This method facilitates community service activities because it goes directly to the field making it easier to find data to write down. This activity ran smoothly because it received a good response from the students as seen from the attitude of the students who were enthusiastic and enthusiastic while praying.